Use of recycled concrete aggregate in concrete: a review - Safiuddin, Md.; Alengaram, Ubagaram Johnson; Rahman, Md. Moshiur; Salam, Md. Abdus; Jumaat, Mohd. Zamin (Journal of Civil Engineering and Management, 2013)
The use of recycled concrete aggregate (RCA) in concrete as partial and full replacements of natural coarse aggregate is growing interest in the construction industry, as it reduces the demand for virgin aggregate. In addition, the use of RCA leads to a possible solution to the environmental problem caused by concrete waste and reduces the negative environmental impact of the aggregate extraction from natural resources. This paper presents a comprehensive review on the use of RCA in concrete based on the experimental data available in the published research. The most important physical, mechanical, and chemical properties of RCA are discussed in this paper. However, more emphasis has been given to discuss the effects of RCA on the fresh and hardened properties and durability of concrete. This paper also identifies the gaps existing in the present state of knowledge on RCA and RCA concrete and provides some recommendations for future research. First punlished online: 24 Oct 2013